(untitled) (Research, Society and Development, 2020)
Objective: to identify and compare the presence of suicidal behavior among crack and alcohol users. Method: quantitative, transversal, descriptive and analytical approach. Data collection took place through interviews with 105 patients allocated in two groups according to the psychiatric clinical diagnosis, in the Alcohol group and the Crack group. Results: Sociodemographic characteristics differed significantly between groups in relation to age (p <0.05). A greater number of patients in the Crack group had suicidal ideation 14 (26.9%) and a previous suicide attempt 18 (34.6%), when compared with the Alcohol group in suicidal ideation 8 (15.1%) and attempted suicide. suicide 15 (28.3%). Logistic regression analysis found no significance in the type of drug as a predictor of suicidal ideation (p = 0.14) and attempted suicide (p = 0.48). Conclusion: when identifying and comparing the presence of suicidal behavior among crack and alcohol users, it was noticed the predominance of suicidal behavior more present in crack users.